Frontotemporal structure preservation underlies the protective effect of lifetime intellectual cognitive reserve on cognition in the elderly - Dandan Wang; Xin Li; Mingxi Dang; Shaokun Zhao; Feng Sang; Zhanjun Zhang (Alzheimer’s Research & Therapy)
Abstract Background Cognitive decline with age has heterogeneous, which might be related to the accumulation of protective factors called cognitive reserve, especially intellectual engagement factors over the life course. However, how lifetime intellectual cognitive reserve (LICR) protects cognitive function in the elderly remains unclear. We aimed to examine the relationship between LICR and cognition and the mild cognitive impairment (MCI) risk, as well as the neural mechanism of LICR on cognition. Methods A total of 5126 participants completed extensive neuropsychological tests, with LICR indicator encompassing early education, midlife occupational complexity, and mental leisure activities after retirement. Confirmatory factor analysis was performed to derive LICR score and cognitive function scores, then the hierarchical regression analysis was used to explore the relationship between LICR and cognitive functions and the risk of MCI. We further explored the macro- and micro-structural preservation underly LICR in 1117 participants. Multiple regressions and tract-based spatial statistics were used to explore the relationship between LICR and gray matter volume and white matter microstructure (FA value). Finally, using the mediation model to explore the relationship of “LICR-brain-cognition”. Result The new LICR index, which was more protective than its single indexes, could protect widespread cognitive functions and was associated with a reduction in MCI risk (Odds Ratio, 0.52; 95% CI, 0.47–0.57). For the structure basis of LICR, the higher LICR score was associated with the greater gray matter volume in right fusiform gyrus (t = 4.62, FDR corrected, p < 0.05) and left orbital superior frontal gyrus (t = 4.56, FDR corrected, p < 0.05), and the higher FA values in the frontotemporal related white matter fiber tracts. Furthermore, the right fusiform gyrus partially mediated the relationship between LICR and executive processing ability (β = 0.01, p = 0.02) and general cognitive ability (β = 0.01, p = 0.03). Conclusions The new comprehensive cognitive reserve index could promote the temporal macro-structural preservation and thus contribute to maintain better cognitive function. These findings highlight the importance of intellectual CR accumulation over the life course in successful cognitive aging and MCI prevention, thereby contributing to improve the quality of life in the elderly.